A Study of Abrar-ul- Haq's Punjabi Bhangra Songs in Pragmatics - Muhammad Ali Shahid; Anser Mahmood; Syeda Iqra Shabbir; Habib Ullah Habib (CV. Rustam, 2023)
The study of language and culture is known as linguistic anthropology. Etymological human sciences have become an interdisciplinary subject of study by utilizing the theoretical underpinnings of numerous disciplines. The current study investigated Punjabi songs using a qualitative analytical approach. The Relevance Theory of Pragmatics, proposed by Deirdre Wilson and Dan Sperber (2004), explained how Abrar-ul-Haq appeared on the horizon to promote Punjabi culture through his energetic Punjabi Bhangra songs. For this study, only two songs were chosen: Billo Day Ghar and Beh Ja Sakal Tay. The study’s findings revealed that Abrar ul Haq used singing as a medium of language to transport cultural norms in general and Punjabi culture in particular. Because he was a famous and world-famous singer, his message spread worldwide, and he became known not only as the Bhangra singer but also as the anthropologist who invented and promoted Punjabi culture through his singing. It is concluded that Punjabi Culture is rich in norms and values. MPhil scholars will expand the scope of the study to include a full-length version of these to promote Punjabi culture. It is suggested that other linguists investigate Punjabi culture to revive and preserve it.